2021
DOI: 10.3390/molecules26082206
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed In Situ Protein Profiling with High-Performance Cleavable Fluorescent Tyramide

Abstract: Understanding the composition, function and regulation of complex cellular systems requires tools that quantify the expression of multiple proteins at their native cellular context. Here, we report a highly sensitive and accurate protein in situ profiling approach using off-the-shelf antibodies and cleavable fluorescent tyramide (CFT). In each cycle of this method, protein targets are stained with horseradish peroxidase (HRP) conjugated antibodies and CFT. Subsequently, the fluorophores are efficiently cleaved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…Subsequently, the fluorophores were cleaved using a mild chemical reaction with 1,3,5-triaza-7-phosphaadamantane (PTA) and tris(2-carboxyethyl)phosphine (TCEP). Following signal removal, almost all the staining signals were erased, confirming the high cleavage efficiency of the CFT as we reported before [22]. We also documented that this chemical reaction does not damage the epitope integrity, which allows other proteins to be accurately profiled in later cycles.…”
Section: Efficient Antibody Stripping While Preserving Epitope Integritysupporting
confidence: 84%
See 2 more Smart Citations
“…Subsequently, the fluorophores were cleaved using a mild chemical reaction with 1,3,5-triaza-7-phosphaadamantane (PTA) and tris(2-carboxyethyl)phosphine (TCEP). Following signal removal, almost all the staining signals were erased, confirming the high cleavage efficiency of the CFT as we reported before [22]. We also documented that this chemical reaction does not damage the epitope integrity, which allows other proteins to be accurately profiled in later cycles.…”
Section: Efficient Antibody Stripping While Preserving Epitope Integritysupporting
confidence: 84%
“…Here we demonstrated that the integrity of the protein epitopes is maintained after at least 20 times of protein stripping. Recently, we also reported that the PTA and TCEP treatment does not damage the epitopes [22]. These results suggest more than 20 analysis cycles can be performed on one tissue sample.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Integrated in situ analysis of RNA and proteins in the same specimen is of increasing importance in studies of gene expression regulation [ 29 ] and disease diagnosis [ 30 ]. Our laboratory recently developed cleavable fluorescent probes [ 27 , 31 , 32 , 33 ] for multiplexed protein imaging and demonstrated that these probes enable a large amount of different proteins to be accurately quantified in their native cellular contexts in single cells. To evaluate whether the multiplexed RNA and proteins in situ analysis can be combined in the same tissue using CFT, we stained two proteins and five mRNA sequentially using tyramide-N 3 -Cy5 in a mouse spinal cord tissue ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…TSA and ABC can amplify fluorescence signals more than eighty and sixfold, respectively 9 , 10 . However, these two techniques rely on a single chemistry, and for multiplexed signal amplification, the signal amplification process needs to be repeated multiple times for each signal 7 , 11 . Conversely, oligonucleotide-based signal amplification can simultaneously amplify multiple fluorescence signals with the target proteins labeled with oligonucleotide-labeled antibodies and the hybridization of fluorophore-conjugated complementary oligonucleotides 8 .…”
Section: Introductionmentioning
confidence: 99%